Uji Efektivitas Ekstrak Daun Serai Wangi (Cyombogonardus L) Dengan Metode Sprayer Terhadap Kematian Rayap Pekerja - Khaer, Ain; Rostina, Rostina; Wulan, Diah Nawang; Haerani, Haerani (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Natural pesticides are derived from plants and contain active compounds produced through secondary metabolism. These compounds possess one or more biological actions that can effectively control insects. Lemon grass (Cymogonardus L) is a natural insecticide that contains various compounds, including a volatile essential oil. This liquid is effective in killing termites by harming their respiratory system and suppressing their appetite. The research aimed to assess the efficacy of citronella leaves (Cyomogonardus L) as a botanical insecticide in eradicating termites. The research methodology employed is quasi-experimental, explicitly utilizing the spray method. This study used a sample size of 20 termites subjected to citronella leaf extract at 4%, 5%, and 6%. Control groups were also included, and the mortality rate of all groups was monitored every 15 minutes for 1 hour over three treatments. The findings demonstrated that the citronella leaf extract, when used at a concentration of 4%, resulted in the mortality of 12 mice (60%). Similarly, at a concentration of 5%, the extract caused the death of 16 mice (80%), while at a concentration of 6%, it led to the death of 17 individuals (85%). In contrast, the control group did not experience termite mortality, indicating the absence of citronella leaf extract administration. Research findings suggest that citronella leaf extract could exterminate termites. The study found that the citronella leaf extract concentrations of 4%, 5%, and 6% were tested, and only the concentrations of 5% and 6% showed effectiveness. According to the research findings, it can be inferred that citronella leaf extract is successful when its concentration is equal to or greater than 80%. It is recommended that the general population utilize citronella leaf extract for termite control, and additional studies on this topic are encouraged Keywords : Termites, Lemongrass Leaves, Essential Oil, Spray Method